Addressing the Threat of Chronic Diseases in Oman - Jawad A. Al-Lawati, MD, MPH; Ruth Mabry, MPH; Ali Jaffer Mohammed, MD, MRCGP (I) (Centers for Disease Control and Prevention, 2008)
IntroductionThe overall health status of the Omani population has evolved over the past 4 decades from one dominated by infectious disease to one in which chronic disease poses the main challenge. Along with a marked reduction in the incidence of infectious diseases, improvements in health care and socioeconomic status have resulted in sharp declines in infant and early childhood mortality and dramatic increases in life expectancy. MethodsFocusing on the time period from 1990 through 2005, we reviewed relevant epidemiological studies and reports and examined socioeconomic indicators to assess the impact of the changing disease profile on Oman's economy and its health care infrastructure.ResultsOver the next 25 years, the elderly population of Oman will increase 6-fold, and the urbanization rate is expected to reach 86%. Currently, more than 75% of the disease burden in Oman is attributable to noncommunicable diseases, with cardiovascular disease as the leading cause of death. The distribution of chronic diseases and related risk factors among the general population is similar to that of industrialized nations: 12% of the population has diabetes, 30% is overweight, 20% is obese, 41% has high cholesterol, and 21% has the metabolic syndrome. ConclusionUnless reforms are introduced to the current health care system, chronic diseases will constitute a major drain on Oman's human and financial resources, threatening the advances in health and longevity achieved over the past 4 decades.